ANALISIS PERMINTAAN OBYEK WISATA PEMANDIAN AIR PANAS KALIANGET, KABUPATEN WONOSOBO DENGAN PENDEKATAN TRAVEL COST - Fanita Osha Tazkia; Banatul Hayati (Universitas Diponegoro, 2012)
ABSTRACT Kalianget Hot Water Spring is one of the tourism potential in the Wonosobo regency because it has the second largest number of visitors established after Dieng. This research aims to determine the factors that influence the demand for visits to Kalianget Hot Water Spring by using the individual travel cost method (ITCM). Regression analysis was involved in this study with specification of the number of individual visits as the dependent variable and the six variables as independent variables. Variables of travel cost to Kalianget Hot Water Spring, travel cost to Dieng, the average family income per month (Rp), distance (Km), group visits and purpose of the visit. The results showed two variables influence the number of tourism demand to the Kalianget Hot Water Spring, the travel cost to the Kalianget Hot Water Spring and monthly family income. Consumer surplus value obtained for Rp 469.475 for each individual year or Rp 93.895.2 each individual visit. The benefit of the Kalianget Hot Water Spring was Rp 93,895,2 for each individual visit. This number is still higher than the average expenditure of visitor Rp 40.662.5. Therefore, the development of Kalianget Hot Water Spring for improvement but also in optimizing the management of its potential.